Pancreas transplantation prevents cellular oxidative stress in kidneys of alloxan-induced diabetic rats - Spadella, César Tadeu [UNESP]; Machado, José Lucio Martins [UNESP]; Lerco, Mauro Masson [UNESP]; Ortolan, Erika Veruska Paiva [UNESP]; Marques, S. F. G. [UNESP] (Elsevier B.V., 2008)
Purpose. Oxidative stress is one of the most important mechanisms to explain genesis of the complications in the chronic progression of diabetes. In this investigation we studied the effects of pancreas transplantation (PT) on the imbalance caused by excessive production of free oxygen radicals by antioxidant defenses of rats with serious chronic hyperglycemia induced by alloxan.Methods. Ninety inbred male Lewis rats were randomly distributed into three groups: NC-30 nondiabetic controls; DC-30 diabetic controls without any treatment; PT-30 diabetic rats undergoing syngeneic PT from normal donor Lewis rats. Each experimental group was then split into three subgroups of 10 animals for sacrifice after 1, 3, or 6 months. Clinical and laboratory parameters from all rats as well as lipid hydroperoxide (LPO) concentrations and renal tissue enzyme activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) were recorded for all rats.Results. Successful PT corrected clinical and laboratory alterations in diabetic rats with sustained normoglycemia throughout the study. A significant increase in LPO concentration and a marked reduction in SOD and CAT enzyme activity were observed in DC rats; there was no significant variation in renal tissue GSH-Px in this group. However, alterations in DC rats were completely restored from 1st month after PT; all evaluated enzyme levels did not significantly differ (P < .01) from those in NC controls.Conclusion. Successful PT controlled cellular oxidative stress in diabetic kidneys, which may prevent chronic lesions.